Development of Football Materials for Middle School Physical Education Teachers Using the ISpring Application - Kurniawan, Ari Wibowo; Kuncoro, Moh. Sufiga; Setiawan, Andy (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
Learning is an interaction between teachers and students. In carrying out learning, the teacher must be able to present the enthusiasm of students when learning, and one of them is when learning physical education. Physical education is learning that is carried out through physical activity, one of which is when learning physical education football material. This study uses the research and development model, using several steps of model development. The purpose of this study was to develop soccer learning materials using an application for MGMP Physical education teachers in the Kediri district so that MGMP Physical Education teachers would find it easier when learning. Data obtained showed that 87% of learning experts, 68% of football experts, and 100% of media experts gave an assessment of this application in a very good category. This study involved 40 subject teacher respondents who were divided into ten teachers to be used as respondents for small group product trials and 30 teachers to conduct large group trials. Based on the sum of all data analysis, it can be concluded that this product is very valid to be used as a learning support tool to help Physical Education teachers in Kediri Regency in conducting learning.